Influence of Medication-Induced Preconditioning or Remote Ischemic Preconditioning on the Intrinsic Vascular Extracellular RNA/Ribonuclease System in Cardioprotection - Tolkmitt, Konstantin J.; Simsekyilmaz, Sakine; Schipke, Julia; Mühlfeld, Christian; Preissner, Klaus T.; Böning, Andreas (The Thoracic and Cardiovascular Surgeon, 2019)
Background It has been demonstrated that remote ischemic preconditioning (RIPC) increases ribonuclease (RNase) levels and protects the heart by reducing extracellular ribonucleic acid (eRNA). As medication-induced preconditioning (MIPC) is also a powerful tool for cardioprotection, we examined the influence of both types of preconditioning on the eRNA/RNase system.Methods In 17 male rats, RIPC (3 × 5 minute hind-leg ischemia) or MIPC (isoflurane and buprenorphine anesthesia) was performed. Five rats served as control and did not undergo preconditioning (non-MIPC). After preconditioning, eRNA levels and RNase activity were determined in plasma, and the hearts were mounted on a blood-perfused Langendorff ischemia/reperfusion apparatus. Hemodynamic, metabolic, and electron microscopic parameters were determined. Furthermore, MIPC with one anesthetic drug only (isoflurane, buprenorphine, or etomidate) was induced in another five rats. After 30 minutes, eRNA levels and RNase activity were determined and compared with an RIPC group (n = 5).Results The plasma of RIPC-treated rats had higher RNase activity and lower eRNA levels than that of MIPC-treated rats. In addition, RIPC increased RNase activity more than MIPC with one drug alone. The RNase activity and eRNA levels in these MIPC groups differed considerably. Hemodynamic parameters of RIPC- and MIPC-treated hearts were better preserved after 90-minute ischemia than those of non-MIPC hearts. No obvious differences were noted between MIPC and RIPC regarding hemodynamics, metabolism, or structural parameters.Conclusions Our results suggest that RIPC does not have any additional cardioprotective benefit in this experimental system. However, the influence of RIPC on the eRNA/RNase system was greater than that of MIPC.
Keywords: myocardial protection/cardioplegia; ischemia/reperfusion; organ preservation; anesthesia